Effectiveness of an educational software system (Desire2Learn) in teaching English grammar - Khan, Mohammad Seemab; Fatimah, Ali; Mustafa, Ghulam; Farooqi, Shahzad-ul-Hassan (AWEJ.org, 2018)
Computer Assisted Language Learning (CALL) has brought enormous developments in teaching and learning process recently. Teaching with computer technology using different methodologies is one of the widely investigated areas in education sector nowadays. This research aims at exploring the efficacy of Computer Assisted Language Teaching (CALT) using Desire2Learn (D2L) Educational software, for teaching subject-verb agreement deductively at Al-Majma’ah University in Saudi Arabia. This study also investigates the attitude of Saudi EFL learners towards CALT-D2L’s effect on their learning achievement. Sixty nine undergraduate students of level three from Department of English, College of education, Al-Majmaah University, were involved in this study. The sample was divided into two groups: (CALT-D2L “Experimental Group” while the other traditional chalk and talk method based as “Control Group”. Analysis of the data of both groups indicates that experimental group outperformed control group in term of the percentage of result compared. Moreover students exhibit positive attitude towards using D2L software in grammar learning.